Sam's sunflower - Powell, Jillian; Boccardo, Johanna (London : Franklin Watts, 2007)
Brightly illustrated stories under 80 words with large text format by top authors and illustrators. Perfect for newly independent readers; text and images interact to help develop visual literacy.
Keywords: Children's picture - book; English - fiction